Climatic factor influencing dengue occurences: evidences from Kota Kinabalu Coastal area / Mohamad Azrin Roslan - Roslan, Mohamad Azrin (2018)
Dengue is the most common mosquito-borne viral disease in the world. In Malaysia, death toll increases over the last decade. However, scarce studies have been done between the relationship of dengue occurrences and climate change especially in Sabah. A laboratory experiment has been conducted to investigate the effect of several climate factors on the rate of life cycle of Aedes aegypti. In real- time event, time series data from 2011 to 2016 of Department of Meterology and Vector control were analysed to study climate factors towards occurrences of dengue. This study suggests that in high temperature with high humidity the rate of life cycle of Aedes aegypti decrease, prompting faster accumulation of this vector. In addition, this study also suggests that in the rainy season dengue occurred significantly (p< 0.05) compared to other weather. Further analysis of the error deviation was also conducted in this study and it shows there is a great potential for forecasting the occurrences of dengue outbreak in the future.